THE INFORMATION SYSTEM FOR A PROJECT MANAGEMENT APPROACH SELECTION AND FORMATION - Игорь Владимирович Кононенко; Светлана Юрьевна Луценко (Radìoelektronnì ì komp'ûternì sistemi (Online), 2020)
There are dozens of project management approaches, presented in the form of standards, methodologies, guides. The usage of the approach that best meets the conditions of the project increases the likelihood of its successful completion Choosing an existing approach or creating a specialized guide for managing a specific project is an important and responsible task, especially for large, expensive and critical projects Researchers offer models, methods and recommendations regarding the selection of one of the common approaches to project management that best meets the conditions of the project and its environment. Also, the methods for the formation of specialized approaches to managing large and responsible projects are being developed. To form such approaches, the authors propose combining the components of existing approaches: values and principles, roles and responsibilities, processes, practices, etc., to obtain the greatest positive effect. As a basis for the formation of the approach, a generalized body of knowledge on project management is proposed, which aggregates the components of the most popular project management approaches. An integrated method has been developed to solve the problems of choosing and forming a project management guide. The method involves two main stages: 1) the selection of an existing project management approach, 2) the formation of specialized management by adjusting and modifying the selected basis. The development, addition, and expansion of the generalized body of knowledge, as well as the complexity of the computational procedures provided by the integrated method, necessitates the development of the PMGuide information system for the project management approach selecting and forming. The work presents this information system with a description of its main subsystems and functionality. The correctness of the developed software is confirmed by solving a practical problem. The developed system simplifies working with the contents of the generalized body of knowledge and implements the calculations necessary to select and form an approach to managing a specific project.